THE RELATIONSHIP BETWEEN POVERTY AND EDUCATION IN CAMEROON - LIONEL NWANA A. AWASUNG (Graduate School of International Studies Ajou University, 2012)
ABSTRACT. Cameroon after independence witnessed a steady increase in her growth rate. Between 1961-1985 her economy was flourishing and development was increasing rapidly. Sooner than later she was hit by an economic crisis due to the devaluation of the CFA Franc in 1993.Poverty began creeping into the economy. Salaries were slashed by almost 60% and many civil servants lost their jobs. The whole economy was affected and poverty was around the corner. The education sector was affected. Investment in education was low. Her educational enrolment was low. But then with the Birth of the millennium development goals in the year 2000 her primary enrolment ratio was on the steady increase. Her net primary enrolment ratio stands at 88.7% but her secondary enrolment ratio is at 34%.This thesis thus seeks to explain that primary education is not an issue blocking development in Cameroon as she stands on track to achieve universal primary education by 2015.There are other bulwarks on the path to Cameroons development despite her attaining a high literacy rate and a high primary enrollment ratio.
학위논문(석사)--Graduate School of International Studies Ajou University :국제개발협력과,2012. 2